Rosenthal's Decoding Algorithm for Certain 1-Dimensional Convolutional Codes - Munoz Castaneda, Angel Luis; Munoz-Porras, Jose M.; Plaza-Martin, Francisco J. (IEEE transactions on information theory, 2019)
The performance of Rosenthal's decoding algorithm is measured when it is applied to certain family of 1-dimensional MDS convolutional codes. It is shown that the performance of this algorithm depends on the algebraic structure of the convolutional code we are working with.